A Holistic View of Aging from Ayurveda and Modern Science - Simran; Sachin Sharma (AYUSHDHARA, 2025)
As the global population ages, there is an increasing need for thoughtful and effective approaches to elder care. Ayurveda, the ancient Indian system of medicine, provides a holistic perspective on aging- termed Jara- viewing it as a natural yet manageable process. This article examines how Ayurveda differentiates between natural aging (Kalaja Jara) and premature aging (Akalaja Jara), both of which are influenced by imbalances in the body’s energies (Doshas), the weakening of bodily tissues (Dhatus), and alterations in digestion and metabolism (Agni). Ayurveda’s insights into aging are aligned with many modern scientific theories, including those that address cellular wear and tear, immune system decline, and oxidative stress. What makes Ayurveda particularly relevant today is its proactive approach, offering practical tools to sustain vitality and postpone age-related decline. These tools include rejuvenating treatments called Rasayana therapies, seasonal detox methods known as Panchakarma, herbal remedies for different ages, daily and seasonal routines called Dincharya and Ritucharya, and strategies for mental well-being known as Satvavajaya Chikitsa. By integrating ancient wisdom with contemporary insights, Ayurveda offers a compassionate, preventive, and empowering approach to healthy aging- one that not only seeks to extend lifespan but also enhances the quality of life.